Depressão, autoestima e satisfação conjugal no ciclo gravídico puerperal: implicações para a maternidade - COSTA, ALINE OLIVEIRA DA (2018)
The present study aimed to investigate and describe the affective, relational, and clinical experiences during the pregnant-puerperal cycle and to analyze the impact of these experiences during the puerperium. In order to do so, four cases were qualitatively selected from a statistical review derived from a project entitled: "Elective caesarean section, humanized childbirth and obstetric violence — The legacy of these experiences for the mother's emotional and relational life." The project focused on two participants most well-adapted to the transition to motherhood, as well as on two less adapted participants, according to the results of the analysis made through the following instruments: SAF-RC, Rosenberg Self-Esteem Scale, and EPDS. The instruments used were the semi-structured interview and the Drawing-And-Story Procedure with a Theme. In general, the results showed that there is some suffering that is intrinsic to the puerperium. We also emphasize that the spouse's support did not prove to be a determinant for a poor adaptation to motherhood, as all the participants received support from their partner to some degree, and three of them developed an emotional disorder. The experience of obstetric violence at childbirth did not prove to be a determinant of emotional disorder either. However, breastfeeding has proved to be an important factor during the puerperium, when many feelings of helplessness, sadness, and despair have arisen. And body changes were also an important factor during the transition to motherhood, since the two participants with emotional disorders struggled in accepting their body changes, and the well-adapted participants did complained about the new body shape. Therefore, we emphasize the need to carry out more studies in order to reflect on changes in body image in women during pregnancy. We also emphasize the importance and necessity of structuring breastfeeding assistance programs and implementing public education policies aiming at qualified instruction for breastfeeding and disease prevention in this sense.